Evaluation of noscapine-licorice combination effects on cough relieving in COVID-19 outpatients: A randomized controlled trial - Barati, Saghar; Feizabadi, Faezeh; Khalaj, Hakimeh; Sheikhzadeh, Hakimeh; Jamaati, Hamid R.; Farajidavar, Hirad; Dastan, Farzaneh (Frontiers in Pharmacology, 2023)
Background: As February 2023, SARS-CoV-2 is still infecting people and children worldwide. Cough and dyspnea are annoying symptoms almost present in a large proportion of COVID-19 outpatients, and the duration of these symptoms might be long enough to affect the patients' quality of life. Studies have shown positive effects for noscapine plus licorice in the previous COVID-19 trials. This study aimed to assess the effects of the combination of noscapine and licorice- for relieving cough in outpatients with COVID-19. Methods: This randomized controlled trial was conducted on 124 patients at the Dr. Masih Daneshvari Hospital. Participants over 18 years of age with confirmed COVID-19 and cough were allowed to enter the study if the onset of symptoms was less than five days. The primary outcome was to assess the response to treatment over five days using the visual analogue scale. Secondary outcomes included the assessment of cough severity after five days using Cough Symptom Score, as well as the cough-related quality of life and dyspnea relieving. Patients in the noscapine plus licorice group received Noscough® syrup 20 milliliters every 6 hours for five days. The control group received diphenhydramine elixir seven milliliters every 8 hours. Results: By day five, 53 (85.48%) patients in the Noscough® group and 49 (79.03%) patients in the diphenhydramine group had response to treatment. This difference was not statistically significant (P-value = 0.34). The presence of dyspnea was significantly lower in the Noscough® group versus diphenhydramine at day five (1.61% in the Noscough® group vs. 12.9% in the diphenhydramine group; P-value = 0.03). The cough-related quality of life and severity also significantly favored Noscough® syrup (P-values <0.001). Conclusion: Noscapine plus licorice syrup was slightly superior to diphenhydramine in relieving cough symptoms and dyspnea in the COVID-19 outpatients. The severity of cough and cough-related quality of life were also significantly better in the noscapine plus licorice syrup. Noscapine plus licorice may be a valuable treatment in relieving cough in COVID-19 outpatients.